A molecular approach to the synthesis of platinum-decorated mesoporous graphitic carbon nitride as selective CO2 reduction photocatalyst. Issue 50 (August 2021) - Tasbihi, Minoo; Fresno, Fernando; Álvarez-Prada, Ignacio; Acharjya, Amitava; Thomas, Arne; Escriche, Lluís; Romero, Nuria; Sala, Xavier; de la Peña O'Shea, Víctor A.; García-Antón, Jordi
Graphical abstract: Highlights: Molecular approach to obtain carbon nitride decorated with platinum nanoparticles. Increased CO2 conversion when Pt nanoparticles are deposited onto carbon nitride. Improved photocatalytic CO2 reduction selectivity compared to bare carbon nitride. Abstract: Platinum nanoparticles (Pt-NPs) have been directly synthesized through the organometallic approach onto the surface of mesoporous graphitic carbon nitride (mpg-CN) semiconductor with two different metal loadings. Thorough multi-technique characterization reveals a very good dispersion of nanoparticles with a narrow size distribution centered at ca. 2.5 nm, regardless of the metal loading, and composed primarily of platinum metal with a minor contribution of oxidic surface species. Compared to bare mpg-CN, the Pt-NPs decorated materials show improved charge separation properties upon band gap excitation, ascribed to electron extraction by Pt-NPs from the conduction band of mpg-CN, as demonstrated by time-resolved fluorescence measurements. The so-obtained materials show photocatalytic activity for CO2 reduction under both UV and visible light irradiation, with improved selectivity towards highly reduced products such as methanol and methane with respect to the bare semiconductor, which leads to the formation of carbon monoxide as the main product. The obtained results shed light on the pathways that determine selectivity in photocatalytic CO2 conversion, contributing to the development of selective photocatalysts, which is one of the cornerstones in this promising technology for direct solar-to-chemical energy conversion.